Collaboration as a Window on What Science Has Come - Turner , Steven (Zagadnienia Naukoznawstwa, 2024)
Agnieszka Olechnicka et al. have nicely documented developments in the internationalization of science and collaboration which raise important broader question. The traditional view, elaborated by Michael Polanyi, was that the transmission of science at the level of discaverers required personal contact, which normally inovolve time spent in laboratories of famous scientists, and hands-on experience with experiments and close interaction with collegues, which in turn implied a few international centres. Has this changed through digitalization and the internet? One change is the increase in teamwork and the size and physical distribution of research teams, the outsourcing to the larger world of "open science", as well as novel forms of funding of collaboration, which creates the need for new arrangements for patents and credit. The huge size of the grant system and other funding for science from discovery and internal competition to "impact", which has inevitable effects on quality and the life-world orientation of scientists. Whether this has improved science is an open question: it has radically changed it.